2018
DOI: 10.1002/jso.25209
|View full text |Cite
|
Sign up to set email alerts
|

NARCA: A novel prognostic scoring system using neutrophil‐albumin ratio and Ca19‐9 to predict overall survival in palliative pancreatic cancer

Abstract: Combining NAR and Ca19-9 into a prognostic score allows stratification of unresectable PDAC patients into groups with significantly different overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 25 publications
5
50
0
Order By: Relevance
“…Serum albumin protects the kidneys from toxic substances and maintains optimal colloid pressure to ensure renal perfusion [30]. Tawfik et al [12] and Tingle et al [13] suggested that NAR is an independent prognostic marker for survival in patients with solid tumors. e findings of the present study suggested that NPAR was an independent predictor of all-cause mortality in critically ill patients with AKI and was a better predictor than neutrophil percentage or albumin alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum albumin protects the kidneys from toxic substances and maintains optimal colloid pressure to ensure renal perfusion [30]. Tawfik et al [12] and Tingle et al [13] suggested that NAR is an independent prognostic marker for survival in patients with solid tumors. e findings of the present study suggested that NPAR was an independent predictor of all-cause mortality in critically ill patients with AKI and was a better predictor than neutrophil percentage or albumin alone.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, we hypothesize that neutrophil percentage-to-albumin (NPAR) could serve as an inflammation-based prognostic score. Neutrophil-to-albumin ratio (NAR) has been identified as a biomarker predicting prognosis in patients with rectal cancer and end-stage pancreatic cancer [12,13]. Based on these findings, we have reason to speculate that NPAR may affect the prognosis of AKI in critical illness.…”
Section: Introductionmentioning
confidence: 99%
“…24 In this study, alongside CAR and CBC-derived biomarkers of inflammation, we also focused on the neutrophil/albumin ratio (NAR), which has recently only been studied in patients with cancer, because higher NAR indicates an enhanced inflammatory status that worsens cancer prognosis and treatment response. 25 Likewise CAR, NAR has not been examined in psychiatric disorders to date. In this study, our aims were as follows: 1) to examine CAR and NAR as novel peripheral inflammatory markers in patients with both acutely exacerbated and remitted schizophrenia, and to compare them between patient and control groups; 2) to reveal whether peripheral inflammatory markers discriminated patients and controls and whether these markers varied between patients with acute exacerbation and remission; and 3) to determine optimum cutoff levels of CAR and NAR for the diagnosis of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 113 studies was identified and screened for eligibility ( Figure S3 ). Eighteen studies, including ours, reported on the prognostic value determined at diagnosis of either CEA, CA19-9 serum levels or both on survival in PDAC patients ( Table S3 ) [ 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Several cut-off values were used varying from 5–4000 kU/L for CA19-9 and 3–20 µg/L for CEA.…”
Section: Resultsmentioning
confidence: 99%